Effects of 6-month, multimodal exercise program on clinical and gait parameters of patients with idiopathic parkinson's disease: a pilot study - Vitório, Rodrigo [UNESP]; Teixeira-Arroyo, Claudia [UNESP]; Lirani-Silva, Ellen [UNESP]; Barbieri, Fabio Augusto [UNESP]; Caetano, Maria Joana Duarte; Gobbi, Sebastião; Stella, Florindo; Teresa Bucken Gobbi, Lilian [UNESP] (Isrn Neurology, 2011)
This pilot study aimed to identify the effects of a 6-month, multimodal exercise program on clinical and gait parameters in patients with Parkinson's disease. Two groups of participants were enrolled in the study: Trained Group (TG) and Control Group (CG). Individuals in the TG exercised three times a week for 24 weeks (in a multimodal exercise program), while the CG participants maintained their regular activity level. Participants in both the TG and the CG were assessed at pre- and posttest by clinical rates and the spatiotemporal parameters of self-paced walking. The two groups were not significantly different in demographic, clinical, and gait data at baseline. There were no significant differences between groups for clinical data at posttest. The purposed multimodal exercise program has found improvement in some kinematic gait parameters for the TG. Further study in the form of randomized controlled trial would be required to establish effectiveness of the intervention.